Proposed Performance Management System For Department of Transportation West Java Province in Land Transportation Sector - Rahayu, Reni Sri; Wibisono, Dermawan (The Indonesian Journal of Business Administration, 2013)
Land Transportation Sector is part of the Department of Transportation West Java Province which has the authority to handle land transportation in West Java province. Performance of land transportation sector can be measured using indicators that reflect increased land transportation services in accordance with Law No. 22 of 2009. The root of problem obtained from the translation of the issues highlighted faced by the Land Transport Sector was it does not have a data report, it has no measurable performance variables; do not have an adequate system performance, and the difficulty to find data. Objective of this final project is to make a proposal of the performance management system for Department of Transportation West Java Province in Land Transport Sector. Performance management system that the most appropriate is Integrated Performance Management System. The method of collection data is use available literature as the primary data, and conduct a SWOT analysis. Integrated performance management system has three perspectives, namely the output of the organization, internal processes and resource capabilities. Perspective of organizational output using non-financial aspects of 4 measurement indicators and 22 measurement indicators recommendations derived from overseas. Internal process perspective aspects of innovation use 1 indicator and 4 indicators for this aspect of the operation. Perspective of resource capabilities have 6 indicator using human resources aspects, technology resource aspects and organization resources. Every indicator of each aspect made the measurement indicators, responsible person for each indicators, standards and performance targets to be achieved. Performance results can be displayed in the view that the proposal submitted. From the results of subsequent performance to do review of the appeal by Department of Transportation Central Java Province and the Department of Transportation and road & transport East Java Province. Implementation performance management system needs to pay attention Inland transportation Sector: current performance management systems, reporting systems required allocation of resources, dissemination and display the results of performance measurement.Ã‚Â Keywords: PMS, IPMS, Transportation, Land.